METHODOLOGICAL DIFFICULTIES OF STATISTICAL ANALYSIS OF THE SCIENTIFIC POTENTIAL OF RUSSIAN REGIONS - D. Yu. Znamenskiy (Вестник университета)
The article considers the methodology of the analysis of the scientific potential of the regions. The paper notes the importance of an integrated, systemic approach to understanding of the category of scientific potential. The author emphasizes the importance of quantitative indicators of the scientific potential of the regions, amenable to statistical analysis. The study attempts to analyse the key statistical indicators of the development of science used to assess the scientific potential of the regions. As a rule, the list of such indicators is limited to the number of scientific organizations functioning in the region, the volume of their funding, as well as a number of personnel indicators. At the same time, the author notes the narrowness of the exclusively resource-based approach to the assessment of the scientific potential and the need to take into account its other factors: informational, social, financial, etc.